Nutritional Pathways to Prostate Health: A Comprehensive Review of Dietary Influences on Prostatitis, BPH, and Prostate Cancer - Memon, Ayesha Abdul Qadir; Fan, Chenyue; Osama, Muhammad; Wei, Calvin R. (Current Nutraceuticals, 2025)
The present article offers a thorough critical assessment of the intricacies of nutrition and prostatic diseases, including prostatitis, benign prostatic hyperplasia, and prostate cancer. The literature review begins with an overview of the embryology, anatomy, and physiology of the prostate gland before proceeding to examine the aetiology, pathophysiology, and risk factors surrounding these prostate diseases. This work aims to provide a broad systematic analysis of nutrient composition and possible effects on the prostate state, including beneficial and harmful nutrients. The review of the findings consolidates the contemporary data regarding the beneficial effects of certain micronutrients, phytochemicals, and diet patterns, as well as the detrimental effects of high intake of saturated fats, processed meats, and refined carbohydrates. In addition, the paper looks into the synergistic and additive impact of multiple dietary constituents to give an understanding of the possible mode of action in prostate disease prevention and control. Therefore, the purpose of this critical analysis is to provide nutritional advice based on scientific evidence that is helpful in enhancing prostate health and reducing the severity of pathologies connected with it.
Keywords: nutritional intervention